Factors That Control the Formation of Dendrites and Other Morphologies on Lithium Metal Anodes - Frenck, Louise; Sethi, Gurmukh K.; Maslyn, Jacqueline A.; Balsara, Nitash P. (Frontiers in Energy Research, 2019)
Lithium metal is a promising anode material for next-generation rechargeable batteries, but non-uniform electrodeposition of lithium is a significant barrier. These non-uniform deposits are often referred to as lithium “dendrites,” although their morphologies can vary. We have surveyed the literature on lithium electrodeposition through three classes of electrolytes: liquids, polymers and inorganic solids. We find that the non-uniform deposits can be grouped into six classes: whiskers, moss, dendrites, globules, trees, and cracks. These deposits were obtained in a variety of cell geometries using both unidirectional deposition and cell cycling. The main result of the study is a figure where the morphology of electrodeposited lithium is plotted as a function of two variables: shear modulus of the electrolyte and current density normalized by the limiting current density. We show that specific morphologies are confined to contiguous regions on this two-dimensional plot.